2015
DOI: 10.1152/ajpendo.00362.2014
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced fatty acid oxidation in adipocytes and macrophages reduces lipid-induced triglyceride accumulation and inflammation

Abstract: -Lipid overload in obesity and type 2 diabetes is associated with adipocyte dysfunction, inflammation, macrophage infiltration, and decreased fatty acid oxidation (FAO). Here, we report that the expression of carnitine palmitoyltransferase 1A (CPT1A), the rate-limiting enzyme in mitochondrial FAO, is higher in human adipose tissue macrophages than in adipocytes and that it is differentially expressed in visceral vs. subcutaneous adipose tissue in both an obese and a type 2 diabetes cohort. These observations l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(125 citation statements)
references
References 54 publications
8
110
0
Order By: Relevance
“…Our results showed an increased CPT1 protein level in both stressed groups, indicating an elevated energy expenditure in the adipose tissue. Although the primary role of white adipocytes is to store lipids rather than to oxidize NEFA, the presence and activity of CPT1 have been demonstrated in the white adipose tissue of rodents as well as humans [46,47]. The higher CPT1 protein level and consequent increase in the oxidation of NEFA derived from the TG breakdown by HSL in the stressed groups could explain why plasma the NEFA concentration was not elevated in these animals.…”
Section: Discussionmentioning
confidence: 98%
“…Our results showed an increased CPT1 protein level in both stressed groups, indicating an elevated energy expenditure in the adipose tissue. Although the primary role of white adipocytes is to store lipids rather than to oxidize NEFA, the presence and activity of CPT1 have been demonstrated in the white adipose tissue of rodents as well as humans [46,47]. The higher CPT1 protein level and consequent increase in the oxidation of NEFA derived from the TG breakdown by HSL in the stressed groups could explain why plasma the NEFA concentration was not elevated in these animals.…”
Section: Discussionmentioning
confidence: 98%
“…CPT1 catalyzes long-chain fatty acyl coenzyme A and carnitine into acyl carnitine, which facilitates in the oxidation of fatty acids in mitochondria matrix [29]. Malandrino et al found that CPT1A promotes the oxidation of fatty acids in fat cells and macrophages, thus, reducing lipid accumulation and inflammation [62]. Therefore, CPT1A plays a role in the inhibition of fat deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work showed that increased intracellular levels of unsaturated fatty acids (including oleic acid, linoleic acid and arachidonic acid), but not saturated fatty acids, stimulates the production of IL-1α in foam cells, leading to increased inflammation in vivo 41 . Intriguingly, enforced expression of constitutively active CPT1A (which as discussed above, transports long-chain fatty acids into the mitochondria) in macrophage cell-lines increased fatty acid oxidation, reduced lipid accumulation and reduced the production of inflammatory cytokines 42 . Therefore, promoting fatty acid oxidation in inflammatory macrophages may be one approach to reducing their inflammatory potential.…”
Section: Fatty Acid Oxidation and Immune Functionmentioning
confidence: 97%